Hubungan Asupan Karbohidrat Dan Status Gizi Dengan Kadar Glukosa Darah Penderita Diabetes Mellitus Tipe II Di Puskesmas Penebel II Kabupaten Tabanan - Sari, Candra Kusuma; Wiardani, Ni Komang; Sri Sugiani, Pande Putu (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Diabetes Mellitus is one of the main non-communicable diseases (PTM) in society. The prevalence of DM continues to increase which causes various impacts such as high health costs and a decrease in people's quality of life. This study aims to determine the relationship between carbohydrate intake and nutritional status with blood glucose levels in Type II Diabetes Mellitus Patients at Penebel II Health Center, Tabanan Regency. The type of research used is descriptive research, namely research conducted on a set of objects that aims to see a picture of phenomena (including health) that occur in a certain population. The number of samples studied was 44 samples. Carbohydrate intake in the more category, namely 86.4%, carbohydrate intake in the normal category was 9%, and for carbohydrate intake in the less category, 4.6%. Significant value of 0.697 (value of r = 0) so that there is no significant relationship between carbohydrate intake and blood glucose levels. Significant value of 0.124 (value of r = 0) so that there is no significant relationship between nutritional status and blood glucose levels.